Poly(ethylene oxide monomethyl ether)- block-poly(propylene succinate) Nanoparticles: Synthesis and Characterization, Enzymatic and Cellular Degradation, Micellar Solubilization of Paclitaxel, and in Vitro and in Vivo Evaluation - Jäger, Alessandro; Jäger, Eliézer; Syrová, Zdeňka; Mazel, Tomas; Kováčik, Lubomír; Raška, Ivan; Höcherl, Anita; Kučka, Jan; Konefal, Rafal; Humajova, Jana; Poučková, Pavla; Štěpánek, Petr; et al. (Biomacromolecules, 2018)
Polyester-based nanostructures are widely studied as drug-delivery systems due to their biocompatibility and biodegradability. They are already used in the clinic. In this work, we describe a new and simple biodegradable and biocompatible system as the Food and Drug Administration approved polyesters (poly-ε-caprolactone, polylactic acid, and poly(lactic- co-glycolic acid)) for the delivery of the anticancer drug paclitaxel (PTX) as a model drug. A hydrophobic polyester, poly(propylene succinate) (PPS), was prepared from a nontoxic alcohol (propylene glycol) and monomer from the Krebs's cycle (succinic acid) in two steps via esterification and melt polycondensation. Furthermore, their amphiphilic block copolyester, poly(ethylene oxide monomethyl ether)- block-poly(propylene succinate) (mPEO- b-PPS), was prepared by three steps via esterification followed by melt polycondensation and the addition of mPEO to the PPS macromolecules. Analysis of the in vitro cellular behavior of the prepared nanoparticle carriers (NPs) (enzymatic degradation, uptake, localization, and fluorescence resonance energy-transfer pair degradation studies) was performed by fluorescence studies. PTX was loaded to the NPs of variable sizes (30, 70, and 150 nm), and their in vitro release was evaluated in different cell models and compared with commercial PTX formulations. The mPEO- b-PPS copolymer analysis displays glass transition temperature < body temperature < melting temperature, lower toxicity (including the toxicity of their degradation products), drug solubilization efficacy, stability against spontaneous hydrolysis during transport in bloodstream, and simultaneous enzymatic degradability after uptake into the cells. The detailed cytotoxicity in vitro and in vivo tumor efficacy studies have shown the superior efficacy of the NPs compared with PTX and PTX commercial formulations.
Keywords: nádorové buněčné linie; paclitaxel; Mice, Inbred BALB C; Nanoparticles; polypropyleny; micely; Polypropylenes; Mice; polyestery; Cell Line, Tumor; Polyethylene Glycols; Antineoplastic Agents; polyethylenglykoly; ženské pohlaví; protinádorové látky; zvířata; myši inbrední BALB C; nanočástice; Micelles; Polyesters; myši; Succinates; Paclitaxel; Female; sukcináty; Animals